Analyzing the Readiness of Javanese Language Teachers Toward the Implementation of Mobile Learning in Gresik Regency - Sulih Aji Pangestu; Mustaji Mustaji; Citra Fitri Kholidya; Heras Widiyoko; Nurhairunnisah; Sinta Aniati (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
This study analyzes the readiness of Javanese language teachers in Gresik Regency to adopt mobile learning by integrating the Technology Acceptance Model (TAM) and the Mobile Learning Readiness (MLR) framework as a multidimensional conceptual approach. This study provides theoretical and practical contributions by strengthening the literature on teacher readiness for mobile learning in Javanese language education and offering empirical evidence to support targeted digital literacy programs and innovative mobile-based learning for improving instructional quality and preserving local culture. The study employed an exploratory quantitative design involving 26 junior high school teachers using a standardized instrument measuring Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and dimensions of technological, pedagogical, and psychological readiness. Data were analyzed using descriptive statistics and trend pattern analysis. The findings reveal an asymmetry between perceived ease of use and perceived pedagogical usefulness, significantly influenced by age and teaching experience. This study extends empirical evidence within the context of local language education and proposes data-driven intervention frameworks to strengthen teacher capacity in sustainable technology integration.